A linguagem mental de Guilheme de Ockham: Contribuições frente ao Externalismo Contemporâneo - Ferreira, Anderson D'arc (2010)
Taking as a starting point for issues of contemporary debate about externalismo in Philosophy of Mind, this paper intends to propose a dialogical possibility of externalism with the structure of mental language ockhamiana. By adopting their line-logical semantics in the field of nominalism, Ockham describes the need relational structures of our subjective with the outside world to mind of the knowing subject. The way he lays the formation and connection of signs to the words and concepts requires the contact of the intellect with the world outside the structures of the agent's subjective knowledge. The work will be divided into three parts. In part I present the entire system and determines which involves the construction of the system ockhamiano. In Part II I discuss the contemporary debate about externalism in philosophy of mind. In Part III I present my vision of how we fit into the Ockham externalist theories in philosophy of mind.